Kernel composition in sorghum landraces revealed via analyses of genotype-by-environment interactions - Chalachew Endalamaw; Dagmawit Tsegaye; Angeline van Biljon; Liezel Herselman; Maryke Labuschagne (PLoS ONE, 2025)
Sorghum stands out among cereals due to its rich bioactive compound content and resilience to varying climates, addressing common issues such as protein, iron (Fe), and zinc (Zn) deficiencies in humans. This study aimed to determine the impact of the genotype, environment, and their interaction on the chemical and physical properties of sorghum grain across locations and seasons. A total of 361 sorghum landraces and four commercial checks were grown for two consecutive seasons from 2020 to 2021 at Melkassa (MK20 and MK21), Jimma (JM20 and JM21) and Miesso (MS20 and MS21). Using genotype main effects with genotype by environment interaction (GGE) ranking biplots, stable and high-performing genotypes were identified. MK21 emerged as an ideal environment for starch, while MS20 proved representative for protein content. For Fe content, environments MS21, MK20, and MK21 were representative, while MS20 and JM20 were discriminatory. MS21 was identified as the most representative for Zn content. These findings underline the diverse and specific performance of sorghum genotypes across various environmental conditions and traits. This study identified sorghum landraces with high and stable starch and protein content, as well as high and stable concentrations of Fe and Zn. Notably, genotypes like G358, G218, G221, G161, and G171 were noted for their high mean protein contents and stability. Genotypes such as G175, G248, G137, and G142, which demonstrated superior performance in Fe, and Zn content, are regarded as excellent candidates for further evaluation and incorporation into breeding programs, offering significant potential to enhance nutritional stability across diverse agroecological regions. Their consistent performance also highlights their potential to address micronutrient deficiencies, contributing to enhanced human nutrition and food security.